Origin and chromatin remodeling of young X/Y sex chromosomes in catfish with sexual plasticity. Issue 2 (28th October 2022) - Gong, Gaorui; Xiong, Yang; Xiao, Shijun; Li, Xi-Yin; Huang, Peipei; Liao, Qian; Han, Qingqing; Lin, Qiaohong; Dan, Cheng; Zhou, Li; Ren, Fan; Zhou, Qi; et al.
ABSTRACT: Assembly of a complete Y chromosome is a significant challenge in animals with an XX/XY sex-determination system. Recently, we created YY-supermale yellow catfish by crossing XY males with sex-reversed XY females, providing a valuable model for Y-chromosome assembly and evolution. Here, we assembled highly homomorphic Y and X chromosomes by sequencing genomes of the YY supermale and XX female in yellow catfish, revealing their nucleotide divergences with only less than 1% and with the same gene compositions. The sex-determining region (SDR) was identified to locate within a physical distance of 0.3 Mb by FST scanning. Strikingly, the incipient sex chromosomes were revealed to originate via autosome–autosome fusion and were characterized by a highly rearranged region with an SDR downstream of the fusion site. We found that the Y chromosome was at a very early stage of differentiation, as no clear evidence of evolutionary strata and classical structure features of recombination suppression for a rather late stage of Y-chromosome evolution were observed. Significantly, a number of sex-antagonistic mutations and the accumulation of repetitive elements were discovered in the SDR, which might be the main driver of the initial establishment of recombination suppression between young X and Y chromosomes. Moreover, distinct three-dimensional chromatin organizations of the Y and X chromosomes were identified in the YY supermales and XX females, as the X chromosome exhibited denser chromatin structure than the Y chromosome, while they respectively have significantly spatial interactions with female- and male-related genes compared with other autosomes. The chromatin configuration of the sex chromosomes as well as the nucleus spatial organization of the XX neomale were remodeled after sex reversal and similar to those in YY supermales, and a male-specific loop containing the SDR was found in the open chromatin region. Our results elucidate the origin of young sex chromosomes and the chromatin remodeling configuration in the catfish sexual plasticity.